Assessment of High School Students’ Ability to Solve Structured Problems with Ideal Model on Acid-Base - Rokhim, Deni Ainur; Atikah, Atikah; Vitarisma, Isma Yanti; Rahayu, Sri; Muntholib, Muntholib (Orbital: The Electronic Journal of Chemistry, 2023)
Problem-solving is one of the abilities that a student must-have in the 21st century. This is because students’ ability to solve problems is expected to increase their competence of higher-order thinking skills (HOTS). Problem-solving ability can be improved in several ways for example, the use of a certain instructional model, worksheets, and assessment or assessment based on problem-solving. This study aimed to develop and implement structured problem-solving assessment with the IDEAL model on acid-base materials, salt hydrolysis, buffer solutions, and acid-base titrations to examine students’ problem-solving abilities. The instrument development model used adapts the ADDIE model with four steps, namely analysis, planning, development, and implementation. The research sample were 34 high school students in grade 11 in Sidoarjo, East Java. The result is that the problem-solving ability with the lowest percentage are in the acid-base titration material for the Act on strategy indicator at 27.21%, while the highest percentage of skills are found in the buffer solution material for the Explore solution indicator at 89.5%. This study implies that the test instrument for further research is to measure students’ ability to solve structured problems with the IDEAL model on acid and base. This study implies that the test instrument for further research measures students’ ability to solve structured problems with the IDEAL model on acid-base, salt hydrolysis, buffer solution, and acid titration. So that the problem solving process with the integration of problem solving problems can improve students’ critical thinking.